Gut Health and Microbiota in Out-of-Season Atlantic Salmon (Salmo salar L.) Smolts Before and After Seawater Transfer Under Commercial Arctic Conditions: Modulation by Functional Feed Ingredients - Wang, Jie; Jaramillo-Torres, Alexander; Li, Yanxian; Brevik, Øyvind Jakobsen; Jakobsen, Jan Vidar; Kortner, Trond M.; Krogdahl, Åshild (Frontiers in Marine Science, 2022)
Atlantic salmon (Salmo salar L.) undergo great alterations in physiology and gut microbiota composition throughout their life stages. This study assessed gut health and microbiota in out-of-season smolts before and after seawater transfer and modulatory effects of functional feed ingredients under commercial Arctic conditions. The fish were fed two series of diets, one without (Ref diet) and one with a mixture of functional ingredients (Test diet). Both diets varied in nutrient composition as required according to the developmental stage of the fish. For fish in freshwater, the mixture of functional ingredients contained nucleotides and immune stimulants, in seawater nucleotides, DHA, and EPA. Samples were collected four weeks before and four weeks after seawater transfer. Regardless of diet, seawater transfer (seawater compared to freshwater) significantly suppressed fish’s growth rate, condition factor, plasma nutrient levels, digesta bile acid concentrations, expression of genes related to gut immune functions (i.e., cytokines and T-cell markers), and increased intestinal microbial richness and diversity. Seawater transfer also reduced the symptoms of pyloric caeca lipid malabsorption with a corresponding decreasing effect on perilipin-2 (plin2) expression. In the gut microbiota of fish in freshwater, the unclassified Ruminococcaceae family dominated strongly, accounting for about 85 % of the total abundance, whereas in seawater the genera Lactobacillus and Photobacterium were the dominant taxa, accounting for about 90 % of the total abundance. Multivariate association analysis showed that relative abundance of certain lactic acid bacteria (LAB) correlated positively with expression of important immune genes. Regarding the effects of functional feed ingredients, Test-fed fish in FW showed higher plasma cholesterol levels, and reduced symptoms of lipid malabsorption, suggesting that the mixture of nucleotides and immune stimulants enhanced digestive and absorptive capacity. However, the inclusion of nucleotides, DHA, and EPA affected the SW-fish only marginally. In conclusion, the outcomes of the present study highlight the great reductions in growth and impact on gut health biomarkers after seawater transfer, in this case observed under commercial Arctic conditions, and the promotion of metabolic capacity of Atlantic salmon fed functional ingredients in freshwater, which may shape future best-practices in salmon industry.